Novel biolubricant synthesis: Enhancing the composition of used cooking oil and Callophyllum inophyllum oil by utilizing infrared heating method - Bela Nurulita; Taufiq Bin Nur; Arridina Susan Silitonga; Teuku Meurah Indra Riayatsyah; Deswita; Md Abul Kalam; Nurin Wahidah Mohd Zulkifli; Abdi Hanra Sebayang; Sihar Siahaan; Munawar Alfansury (Results in Engineering)
This study presents a novel biolubricant synthesis method using infrared heating to produce biolubricant from a blend of used cooking oil and Calophyllum inophyllum oil (UCOCI). Response Surface Methodology was applied to optimize the polyesterification process, varying reaction time, ethylene glycol (EG) to UCOCI methyl ester ratio, and sodium methoxide concentration. The predicted biolubricant yield was 94.30 %, closely matching the experimental yield of 94.03 %. The quadratic response model demonstrated a strong fit (R² = 0.9979). Physicochemical and tribological properties were evaluated and compared to SAE 15-W40 lubricant. UCOCI biolubricant showed an acid value of 0.46 mg KOH/g, viscosities of 83.46 cSt at 40 °C and 13.2 cSt at 100 °C, and a viscosity index of 216.32. Friction coefficients of UCOCI biolubricant blends (Biol10 to Biol50) ranged from 0.1091 to 0.071, all lower than SAE 15W-40. The wear scar diameters for these blends (0.140 to 0.100 mm) were also significantly smaller than SAE 15W-40 (0.549 mm). The superior lubricating properties suggest UCOCI biolubricant's potential for use in heavy-duty engines and as a natural additive.